What women want [videorecording (DVD)] - Meyers, Nancy; Meyers, Nancy; Gibson, Mel; Hunt, Helen, 1963-; Tomei, Marisa (Paramount, 2017)
When a freak accident gives a womanizing executive the ability to hear women's thoughts, he first uses his gift to gain an advantage over his newly appointed female boss, but soon finds himself falling in love with her.